Pressure Drop dan Pola Aliran Dua Fase (Air-Udara) Melewati Pipa Groove Vertikal - Aji, Supa Kusuma; Widhiyanuriyawan, Denny; Yuliati, Lilis (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
This research was conducted to observe the effect of adding grooves in the two-phase flow of water-air in the same direction through a vertical pipe to changes in pressure and fluid flow patterns. Test section in the form of pipes with grooves made of acrylic material with a length of 100 cm and an internal diameter of 2.54 cm. The geometric shape of the acrylic pipe is modified by giving a groove in the direction of the pipe along the test section. Grooves used amounted to 4 and 16 and pipes without grooves used as a comparison. Tests are carried out by flowing water and air that has been mixed through the inlet side upward. The ratio of air velocity to water velocity (VG / VL ) is 0.24-1.13. The method used in this study is experimental. Retrieval of pressure drops data is done by using a differential pressure transmitter. Visual observations are also made using a DSLR camera equipped with a flash and video observations using a smartphone with slow-motion mode. The results showed changes in flow patterns and pressure drop values. Slugs in pipes with grooves disappear faster and pressure drops are lower than pipes without grooves.